Novel closed-loop thermal gradient system for sustainable atmospheric water harvesting - Alibrahim, Bashar; Habib, Maan; Habib, Ahed (Springernature, 2025)
Water scarcity and the growing demand for sustainable water production present critical challenges, particularly in arid regions where conventional desalination technologies are energy-intensive and contribute to carbon emissions. This study proposes an innovative closed-loop system for atmospheric water harvesting, leveraging natural thermal gradients between high-altitude and low-altitude locations to condense water vapor from humid air. The system integrates high-thermal-conductivity materials, energy-efficient heat exchangers, and refrigerant fluids to achieve efficient heat transfer, enabling water condensation at minimal environmental cost. Key findings highlight the system's reliance on factors such as temperature lapse rates, material properties, fluid dynamics, and heat exchanger design for optimal performance. Case studies in the Kingdom of Saudi Arabia demonstrated the feasibility of applying this technology in regions with significant elevation differences, with temperature gradients and humidity levels supporting consistent freshwater production. Although quantitative performance metrics vary due to dynamic environmental conditions, the system shows promise in achieving significant reductions in energy consumption by leveraging natural thermal gradients, thereby minimizing reliance on fossil fuels and aligning with global carbon neutrality goals. This research underscores the potential of closed-loop systems as a sustainable alternative for water generation in energy-constrained environments. By addressing both water scarcity and climate change, the study lays the groundwork for further advancements in atmospheric water harvesting technologies and their integration with renewable energy systems.
Keywords: Thermal gradient; Sustainable energy; Freshwater generation; Passive cooling; Carbon reduction